New sociology for better understanding severe eosinophilic asthma: introducing the SOCS family. Issue 3 (September 2016) - Gras, Delphine; Chanez, Pascal
Severe asthma is a heterogeneous condition characterised by a persistent uncontrolled situation with an inadequate response to current therapy [1]. This definition points the serious unmet needs of the patients and an urgent research effort to understand better the mechanisms sustaining this clinical condition for our community. However, severe asthma is still not identified as a distinct entity and is very heterogeneous. At present, several endotypes have been described based on the presence of upregulated cytokines leading to the recruitment, activation and increased survival of inflammatory cells such as eosinophils. One major endotype is related to T2 lymphocyte (T-helper cell type 2 and innate lymphoid cell type 2) activation, which is observed in most severe asthma patients. Fortunately, several new drugs are or have been developed to interfere with this endotype, but there are still important gaps of knowledge to be filled and clearly, other targets should be identified to develop innovative treatments [2]. SOCS proteins' involvement in severe eosinophilic asthma http://ow.ly/lG943023yxZ